2009
DOI: 10.1513/pats.200902-009aw
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Fluorescence Endomicroscopy of the Human Airways

Abstract: Confocal endomicroscopes aim at providing to the clinician microscopic imaging of a living tissue. The currently available microendoscopic devices use the principle of confocal fluorescent microscopy, in which the objective is replaced by an optical fiber and a miniaturized scanhead at the distal end of the endoscope or by a retractable bundle of optical fibers. Such systems have recently been applied to the explorations of several organs, including the gastrointestinal tract, and more recently to the proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 35 publications
0
80
0
5
Order By: Relevance
“…Briefly, a 4.4-mm bronchoscope (MP60 model; Olympus, Tokyo, Japan) was inserted into the airways down to the smallest reachable bronchi. The pCLE miniprobe was then introduced into the working channel of the bronchoscope, and was pushed smoothly beyond the bronchoscope view into the successive divisions of the bronchial tree until it penetrated into a pulmonary lobule, as previously described [15][16][17]22]. pCLE sequences were recorded and stored for subsequent analysis.…”
Section: Diagnosis Of Ildmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, a 4.4-mm bronchoscope (MP60 model; Olympus, Tokyo, Japan) was inserted into the airways down to the smallest reachable bronchi. The pCLE miniprobe was then introduced into the working channel of the bronchoscope, and was pushed smoothly beyond the bronchoscope view into the successive divisions of the bronchial tree until it penetrated into a pulmonary lobule, as previously described [15][16][17]22]. pCLE sequences were recorded and stored for subsequent analysis.…”
Section: Diagnosis Of Ildmentioning
confidence: 99%
“…The procedure enables the exploration of proximal bronchus and alveolar regions during bronchoscopy in real time [15][16][17][18]. Studies have demonstrated that the main endogenous fluorophore, observed with pCLE at 488 nm excitation wavelength, is the elastin, which is a major component of the distal lung interstitial network, present in the axial backbone of the alveolar ducts and alveolar entrances [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…An exploratory method worth mentioning is human in vivo fluorescence microimaging. It provides tremendous detail of the airways up to alveolar ducts and sacs (Thiberville et al, 2009). However, the technique requires bronchoscopy and minute tissue puncture, but without any reported adverse effects.…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 99%
“…Elastin accounts for 50% of connective tissue fibers in peripheral pulmonary (4), possesses the autofluorescent properties with an excitation wavelength of 488 nm (5), which makes it the major visible structure under the exploration of confocal endomicroscopy (6,7). Previous studies reported that confocal endomicroscopy with pCLE probes could detect the changes of elastin composition in the airway and alveolar in the lung cancer tissues (8).…”
Section: Discussionmentioning
confidence: 99%